The Implementation of Hidden Curriculum On Fifth Grade Students' Character Development at Islamic Elementary School - Malahati, Fildza; Rokhimawan, Mohamad Agung (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
Educational institution requires systemized instruments, namely curriculum a to provide and facilitate education. Curriculum is a standard policy for educator to plan experiences in students learning. However, the conventional curriculum is incapable of accommodating all of students' personal needs, which needed to develop their characters. The characters development is core of moral education. A concpet named hidden curriculum is alternative program to develop students' personalities. The purpose of this study was to describe and analyze comprehensively the implementation of hidden curriculum by developing the eighteen characters values at VA Grade students at the Islamic Elementary School of Darussalam Plaosan. The is a Qualitative Research with field research approach that focuses on explaining the phenomenons by determine the data's behavior and knowledge. The data was taken through Data Collection Techniques using questionnaires, interviews, and direct observations. Meanwhile, the Research Method of this study is the Data Analysis that using data reduction, data validity test, data display, and data drawing to conduct the conclusions based on analizing the phenomenon into descriptive forms. The research findings showed that the implementation of hidden curriculum in the education program by developing eighteen characters values can be cateogrized such as religious, good behaviors and persevance also has a dominant positive response that is 89.6%. Then, the results of random interviews with 10 students also showed a form of response to positive behavior that supports the subjective. Meanwhile, the direct observations were conducted at the Islamic Elementary School of Darussalam Plaosan to identify actual forms of implementation of the eighteen characters values. So, it can be defined that the hidden curriculum has advantages to support the development students' characters values. Keywords: Hidden curriculum, Character Development, Islamic Elementary School of Darussalam Plaosan